Reaction probability and kinetics of water splitting on the penta-NiAs2 monolayer from an ab initio molecular dynamics investigation. Issue 32 (7th August 2020) - Ho, Thi H.; Dong, Hieu C.; Bui, Viet Q; Kawazoe, Yoshiyuki; Le, Hung M.
Abstract : The reaction probability and kinetics of the water splitting process on the penta-NiAs2 monolayer are studied using ab initio molecular dynamics simulations. Abstract : The reaction probability and kinetics of the water splitting process on the penta-NiAs2 monolayer are studied using ab initio molecular dynamics simulations. A total of 100 trajectories are investigated, in which a H2 O molecule is set to strike the surface with a translational energy of 1 eV or 2 eV. The results show that the NiAs2 monolayer is an excellent candidate for the activation of water splitting with a reaction probability of 94% for both energy levels. Interestingly, the kinetics of two O–H dissociation stages varies greatly with respect to the inletting translational energy. Interpreting the reaction data for the 1 eV case, we conclude that O–H 1 and O–H 2 dissociations are first-order processes. However, such dissociation steps become pseudo-zeroth order in the 2 eV case. At the time of the dissociation, the force acting on atoms and the principal component analysis suggest that the two OH breaking stages behave like harmonic springs until reaching the dissociation.